Does it pay to be socially connected with wall street brokerages? Evidence from cost of equity - Luong, Thanh Son; Qiu, Buhui; Wu, Yi (Ava) (Journal of Corporate Finance, 2021)
We show that social connections between a firm's executives and directors and brokerages that follow the firm decrease the firm's cost of equity. We use quasi-natural experiments to address endogeneity concerns and find that the uncovered effect of firm-brokerage social connections on cost of equity is likely causal. The effect is found to be more pronounced for firms with more soft information, opaque information environments, tight financial constraints, weak corporate monitoring, or high executive equity ownership. Further, consistent with the evidence on cost of equity, we find that firm-brokerage social connections reduce SEO underpricing, decrease information asymmetry in stock markets, and improve the firm's equity valuation.